GONAD STRUCTURE OF POPULATION AND MATURITY GASTROPODA Telescopium telescopium IN KETAPANG BEACH WATER DESA SUNGAI CINGAM KECAMATAN RUPAT BENGKALIS - Jeprin Hasibuan; Syafruddin Nasution; Afrizal Tanjung (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AstractOne of the biota that lives in mangrove ecosystems is the gastropod telescopium telescopium. Telescopium telescopium has more active behavior at spring tide (high tide and low tide) than low tide (low tide and high low tide). The weight of the gonad will reach a maximum of a moment when the mangrove snail will spawn, then the weight of the gonad will decrease rapidly as long as the spawning is in progress until complete. This research was carried out in June-July 2018, sampling in the mangrove ecosystem of Ketapang Beach waters, Sungai Cingam Village, Rupat District, Bengkalis Regency, Riau Province. The samples were analyzed at the Marine Biology Laboratory of the Faculty of Fisheries and Marine Sciences, Riau University. This study aims to determine the population structure of gonad maturity index and habitat conditions of T. telescopium gastropods in Ketapang Beach waters, Sungai Cingam Village, Rupat District. The method used in this research is survey method. Measurement of water quality parameters is carried out in situ, namely temperature, and determination of sampling locations by purposive sampling, salinity and pH, type of substrate in sandy mud dominance. Water quality parameters are still supportive for the life of mangrove snails. Average density of Tcopcopium T in the mangrove forest of Sungai Cingam Village is low. There were no differences in density between the research stations but there were differences in density between the study zones. The average distribution pattern of T. telescopium is clustered. The size of T. telescopium found ranged from 38-87 mm. The main habitat of T. telescopium is in zone 2 (lowere zone).Keywords: Population structure, Telescopium telescopium, Rupat Island.